Calcifying nanoparticles associated encrusted urinary bladder cystitis - Tomislav M Jelic (Dove Medical Press, 2008)
Tomislav M Jelic1, Rod Roque1, Uzay Yasar2, Shayna B Tomchin1, Jose M Serrato2, Samuel G Deem3, James P Tierney3, Ho-Huang Chang11Department of Pathology Charleston Area Medical Center, Charleston WV, USA; 2Urology Center of Charleston, Charleston WV, USA; 3Urologic-Surgical Assoc. of Charleston, Charleston WV, USAAbstract: Encrusted cystitis is a subtype of chronic cystitis characterized by multiple calcifications in the form of plaques located in the interstitium of the urinary bladder mucosa and frequently associated with mucosal ulcers. It is a very rare disease of controversial etiology. Our transmission electron microscopy of the calcified plaques of encrusted cystitis has revealed that the smallest formed particles (elementary units) of these calcifications are electron-dense shells surrounding an electron lucent core, diagnostic of calcifying nanoparticles (previously called nanobacteria). We pioneer the notion that calcifying nanoparticles are the causative agents of encrusted urinary bladder cystitis.Keywords: calcifying nanoparticles, nanobacteria, encrusted cystitis